Pyrolisis Temperature Effect to the Biochar Product from Chocolate’s Fruit Skin (Theobroma cacao L.) - Abdul Gani Haji; Ibnu Khaldun; . Habibati; Muhammad Nazar; Eka Safrina (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
This research’s aim is to find out the effect of pyrolisis temperature to the biochar product from chocolate’s rind. The sample of rind of 20 kg is come from Indrapuri, Great Aceh. The water level of the sample is determined and then it was pyrolised with pyrolisator at the temperatures of 300, 400, and 500oC. The biochar gotten is then measured its rendemen and characterized which comprised of flying substance level, ash, bonded carbon, nitrogen, phosphor, potassium, and then the chemical substances were identified by using Gas Chromatography-Mass Spectroscopy (GCMS). Pyrolisis product of biochars at the temperatures of 300, 400, and 500oC were gained rendemen of 8.98; 8.45, and 8.35% (w/w) in a row. These biochars have physical appearance of black with brittle texture. It were gained biochars’s characteristic product of water level at 3.93% (300oC), 2.43% (400oC), and 1.50% (500oC) respectively; flying substance level at 47.13% (300oC), 29.58% (400oC) and 25.48% (500oC); ash level at15.70% (300oC), 17.14% (400oC), and 18.02% (500oC), bonded carbon at 37.16% (300oC), 53.37% (400oC), and 56.32% (500oC). The highest level of nitrogen (3.51%) is gained with biochar’s pyrolisis product at the temperature 300oC, meanwhile for the 500 dan 400oC, their nitrogen level are 1.29 and 0.86%. Phosphor level at biochar’s pyrolisis product at the temperature of 300, 400 and 500oC in a row are 0.90; 0.43; 1.39% and potassium level at this biochar are 3.34,4.73, and 4.41% consecutively. GCMS analysis result to the biochar’s pyrolisis product at the temperature of 300oC was identified 40 compounds with their main contents is 4-beta-5-dihydroneronin (22.02%), whereas at the temperatures of 400 dan 500oC respective are identified of 11 and 23 compounds, however their main contents is oleat acid with the level of 62.47 dan 49.84% in a row. It can be concluded that biochar’s characteristics of chocolate’s rind is determined by pyrolisis temperature.